2012
DOI: 10.21608/jpp.2012.84991
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Improvement of Cowpea Under Desert Soil Conditions

Abstract: Two field experiments were carried out in sandy soil during the summer seasons of 2003 and 2004at Siwa Oasis, Egypt (26.0°N, 29.0°E and 0-22 m under mean sea level). The experiments were irrigated by using drip irrigation system with salinity water of 6000 p.p.m), Cowpea, Vigna unguiculata cv. Cream 7 cultivar was cultivated to study the effect of inoculation by three methods (inoculation of seeds pre-sowing, as soil application by injection of inoculation after germination and with both methods on the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The interaction between nitrogen sources and different rates combined with and without bio-fertilizer were significant increases all parameters of plants, except weight of 100 seeds was no significant. [20] reported that the inoculation of cowpea seeds with rhizobia significant increased number pods/plant, number of seeds/pod, seed yield/plant and seed yield/ha compared un inoculation seed.…”
Section: Effect Of Different Sources Nitrogen Fertilizer and Differenmentioning
confidence: 99%
See 3 more Smart Citations
“…The interaction between nitrogen sources and different rates combined with and without bio-fertilizer were significant increases all parameters of plants, except weight of 100 seeds was no significant. [20] reported that the inoculation of cowpea seeds with rhizobia significant increased number pods/plant, number of seeds/pod, seed yield/plant and seed yield/ha compared un inoculation seed.…”
Section: Effect Of Different Sources Nitrogen Fertilizer and Differenmentioning
confidence: 99%
“…This result may be due to the decrease in pH values could be attributed to the production of CO 2 and organic acids by soil microorganisms acting and other chemical transformation on the added bio-fertilizer. Ghodia [20] reported that the soil pH was decreased with increasing N rate by ammonium sulphate and urea fertilizers. Ayub et al [21] found that the applied of ammonium sulphate on saline soil was decreased of soil pH from (8.5 -7.8) after 20 weeks.…”
Section: Soil Phmentioning
confidence: 99%
See 2 more Smart Citations
“…These results may be due to the ammonium sulphate is an essential element of bio-molecules such as amino acids, proteins, nucleic acids, phytohormones and a number of enzymes and coenzymes and improve of yield component [35]. Reported that the inoculation of cowpea seeds with rhizobia significant increased number pods plant -1 , number of seeds pod -1 , seed yield plant -1 and seed yield fed -1 compared with uninoculated seed.…”
Section: Effect Of Different Nitrogen Forms and Application Rates Companied With Bio-fertilizer On Yield Componentmentioning
confidence: 99%